If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2 = 1 Reorder the terms: -2 + 9x = 1 Solving -2 + 9x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 9x = 1 + 2 Combine like terms: -2 + 2 = 0 0 + 9x = 1 + 2 9x = 1 + 2 Combine like terms: 1 + 2 = 3 9x = 3 Divide each side by '9'. x = 0.3333333333 Simplifying x = 0.3333333333
| -7a=6 | | 32x-6=25x | | 93-6x=30x+17 | | -18=12a | | (5)/(6)-(1)/(3)=3 | | y-(-9)=-2/9(3-4/9) | | 5=13t | | 9x/x^2+8x | | r^3-8r^2+16r^2=0 | | 7x^2-265x-600=0 | | 4m+2=29-2m | | -3(x-7)(x-8)= | | 7x^2-265t-600=0 | | -8b=-13 | | -6y-9=2y+15 | | 4y-12=y-12 | | x+2y-3z=9 | | X+24+2x=-19-2x-22 | | -9w=-12 | | -2a+8+6a=9a-3a | | 5a=-2 | | 18x^3-27x= | | 52+5y-21=17y-14-3y | | 3x+4/2x+3=x+14/x+8 | | 20=-6a | | x+3/x+1=x-3/x-8 | | -7r=6 | | 4z-15-z+3=0 | | 62-5x=10x+18 | | -6x=9 | | 4d=8-4d | | 4r=-4 |